Honeypot-Integrated CSIRT Model Based on ISO 27001/27035 - Meinarni, Ni Putu Suci; Udayana, I Putu Agus Eka Darma (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2026)
Higher education institutions are evolving into digital entities that manage critical assets, including sensitive personal data and academic records. However, many universities in Indonesia still lack a structured and legally compliant approach to information security, leaving them vulnerable to cyber threats such as defacement attacks and data breaches. This paper proposes a conceptual model for a Computer Security Incident Response Team (CSIRT) specifically designed for academic environments. The model integrates international standards ISO/IEC 27001 for Information Security Management Systems and ISO/IEC 27035 for incident handling, with proactive threat detection using honeypot technology. The framework consists of four layers: governance, operational procedures, technology infrastructure, and legal compliance. Designed using a systems-thinking approach and validated through expert review, the model addresses institutional readiness and outlines a roadmap for phased implementation. It aims to support early threat detection, structured response workflows, and digital forensic readiness in alignment with Indonesian cybersecurity law. This honeypot-integrated CSIRT model contributes a strategic reference for universities seeking to enhance their security capabilities in a sustainable and lawful manner.